2009
DOI: 10.1017/s1041610209008734
|View full text |Cite
|
Sign up to set email alerts
|

International perspectives on dementia education, training and knowledge transfer

Abstract: Dementia is on the rise and, as a result, the aged care workforce has an increasing need for up-to-date information on how to care for people living with dementia. While dementia research continues to mushroom, any research findings that have practical implications also need to be passed on to those at the coalface of dementia care as quickly as possible. This Supplement brings together a number of papers that have addressed various perspectives on dementia education, training and knowledge transfer in the U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 1 publication
(3 reference statements)
0
13
0
Order By: Relevance
“…A growing literature has shown that physicians and other health professionals can be taught to understand and implement a variety of patient-centered techniques, including demonstrating empathy, asking for patient understanding, and conveying reassurance (LA et al, 2011). When working with patients with dementia, communication skills training is particularly important for health professionals and family caregivers (Doyle, 2009). Systematic reviews in dementia care have demonstrated significant positive effects of communication skills training on professional and family caregivers’ communication skills, competencies, and knowledge (Eggenberger, Heimerl, & Bennett, 2013; Wolff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature has shown that physicians and other health professionals can be taught to understand and implement a variety of patient-centered techniques, including demonstrating empathy, asking for patient understanding, and conveying reassurance (LA et al, 2011). When working with patients with dementia, communication skills training is particularly important for health professionals and family caregivers (Doyle, 2009). Systematic reviews in dementia care have demonstrated significant positive effects of communication skills training on professional and family caregivers’ communication skills, competencies, and knowledge (Eggenberger, Heimerl, & Bennett, 2013; Wolff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are ways to facilitate meaningful interactions in dementia care (Adams and Gardiner, 2005; Killick and Allan, 2008). International reports emphasize that communication skills training and education are particularly important for staff working with people with dementia as well as for family caregivers (NHS, 2005; 2007; Doyle et al ., 2009). The need for and importance of dementia care education has been shown for different professions such as aged care workers (Flemming and FitzGerald, 2009), healthcare assistants in hospitals (Chapman and Law, 2009), and primary care physicians (Cherry et al ., 2009; Beer et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The DLC intervention, developed to strengthen the quality of the residential dementia care environment, combined a number of proven approaches including dementia training incorporating didactic and interactive elements [ 23 , 58 ], continuous improvement processes [ 14 16 ], support through a community of practice [ 14 ], and recognition, coaching and reward of dementia care leadership and organisational culture change [ 10 , 11 ]. This evaluation which tested the underlying DLC assumptions (logic model) about the relationship between these intervention components and the intended outcomes offers evidence for areas where this dementia care practice innovation may be further refined.…”
Section: Discussionmentioning
confidence: 99%
“…One component of the scheme - a training programme (‘Dementia Leadership Award‘) aimed at care home owners, managers and clinical leads - was reported to produce the culture change necessary for understanding and supporting DLWs’ role [ 10 ]. This finding reflects the growing importance of leadership as a concept in dementia education when resource shortages constrain the extent of staff training available and those trained must act as change agents to realise the benefits of this education in practice [ 11 ]. Cultivating leadership, increasing staff knowledge and support, and networking informational resources are all elements of interventions involving ‘dementia champions’, a role which has been employed in various forms in both acute and residential care settings in the UK and elsewhere [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%